Peran Lembaga Pengembangan Tilawatil Qur'an Dan Dakwah (Lptq & D) Dalam Menerapkan Metode Dakwah Pada Mahasiswa Universitas Islam Negeri Raden Fatah Palembang - Elissani Elissani (Social Science and Contemporary Issues Journal, 2023)
The research entitled "The Role of the Tilawatil Qur'an and Da'wah Development Institute (LPTQ&D) in Applying Da'wah Methods to Students of UIN Raden Fatah Palembang".  This research is motivated by the lack of student participation in carrying out da'wah training activities at the Darul Muttqin Mosque of UIN Raden Fatah Palembang, including their lack of participation in training activities, lack of effectiveness of training schedules, lack of student participation in conducting weekly training activities held by LPTQ&D da'wah division, the role of  leader who is still being ignored.  This study aims to determine the role of LPTQ&D in implementing student participation in participating in trainings and participating in religious activities held by LPTQ&D and to find out the inhibiting and supporting factors of LTQ&D in applying the da'wah method to students.  The method used in this research is a qualitative approach to produce descriptive data.  Data collection was carried out by researchers using observation, interviews and documentation methods.  Meanwhile, data analysis uses data reduction, data presentation and conclusions.  In the results of the research conducted by this researcher, it was found that the da'wah activities carried out at the LPTQ&D da'wah division used appropriate and not arbitrary da'wah methods, the Al-Hikmah da'wah method, the Al-Mauidzotil Hasannah da'wah method, the Al-MujJadi Bil-Al-Da'wah method.  Lati Hiyya Ahsan.